(untitled) (Bangladesh Journal of Endosurgery, 2013)
Objective: Laparoscopic excision has now become the standard treatment option for benign ovarian cysts. Stripping is an effective and popular technique practiced by the surgeons for ovarian cyst excision. Use of electro-cautery in the residual ovarian bed is blamed for the reduction of ovarian reserve. Our experience of laparoscopic stripping technique without use of electro-cautery in the remaining ovarian tissue is described. Materials and Methods: From 1 January 2006 to 31 December 2010, 26 cases were considered for laparoscopic stripping ovarian cystectomy. Using mono-polar hook cautery a flap was marked and raised on cyst wall and serous fluid sucked out. A plane was then created between inner and outer linings of the cyst wall, and inner lining peeled off. Warm normal saline wash was then given and the stripped lining was brought out through supra-umbilical port. Patients were followed up at 15 days, 1 month, 3 months, 1 year and then yearly with ultrasonogram at 3 months and 1 year. Patients age, operative time and outcome, blood loss and complications were studied retrospectively. Results: Age ranged from 3.5 to 16 years. Presenting complaints included: abdominal pain (11), abdominal swelling (8) and palpable abdominal lump (7). Average operative time was 40.30 minutes and operative blood loss ranged from 10 to 36 ml. There was no intra or post-operative complication. There was no recurrence of cyst confirmed by ultrasonography at 3 months and 1 year. Conclusions: Avoiding use of electro-cautery during ovarian cystectomy by stripping technique can prevent damage and reduction in ovarian reserve. DOI: http://dx.doi.org/10.11593/bje.2013.0101.0007 Bangladesh Journal of Endosurgery Vol.1(1) January 2013: 26-28